Tata Kelola Rekam Medis Berbasis Elektronik dalam Kasus Pelaporan Pasien COVID-19 dengan Metode Rapid Application Development di RSUD AL IHSAN - Mahendra, Hadid Ubaidillah; Gunawan, Erix; Kurniawati, Rina (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Information on hospitalized patients with COVID-19-19 is available through the Corona Virus Disease 2019 Reporting Information System. As with the problem in every hospital, the officer in charge of collecting COVID-19 patient data is still not effective, such as recording data and lab reports of suspected COVID-19 cases before entering them into the information system using COVID-19 recording forms and Microsoft Excel. This of course results in late and inaccurate data delivery, resulting in difficulties in monitoring the spread of COVID-19 and COVID-19 mitigation programs in hospitals. In this investigation, the researchers used Rapid Application Development (RAD), a software development technique that prioritizes rapid iterations of the development cycle. Development teams can use the RAD methodology to concentrate on prototyping work and then quickly iterate depending on input from users or related parties. With this method, we have more leeway to adapt to future COVID-19-19 reporting requirements and rules. The creation of an information system that allows medical personnel or field personnel to relay case data directly from the scene is an example of the implementation of RAD in COVID-19-19 reporting This allows for proper data collection. The results obtained from the application of methods with problems that occur in COVID-19 reporting cases The process of collecting and reporting COVID-19 data becomes more effective, this system can also help officers in monitoring COVID-19 cases so that they can provide the necessary information to the COVID-19 response team.